Students' Perceptions of Immediate Feedback and Delayed Feedback in Learning Writing - Ajam, Ali; Sahmadan, Safrudin; Budi Lestari , Sri Ayu; Dewi, Ni Putu Juliani Lestari (English Education Department, 2025)
This study stems from the existence of corrective feedback whose timing has become a hotly debated issue and requires further empirical investigation by second language researchers. This needs to be done because related to the ideal time to implement corrective feedback, some studies confirm that immediate feedback has more positive effects and maximizes students' learning opportunities. However, on the other hand, some researchers claim that of the two types of feedback, delayed feedback is more influential and beneficial in students' language development. This study aims to further explore students' perceptions of immediate feedback and delayed feedback in the writing learning process. Descriptive Qualitative Method was carried out in this study by involving 20 students as samples. The instruments used in collecting data are questionnaire and interview. The data analysis technique used is an interactive model consisting of data collection, data filtering, data display and conclusion making or verification. The results of data analysis showed that all responses to immediate corrective feedback were positive as indicated by 66% of students chose strongly agree and 34% chose agree. As for delayed corrective feedback, only 35% of students agreed and the remaining 65% disagreed.